Development of a Guided Discovery-Based Scientific Approach Module for Enhancing Problem-Solving Skills - Wantoro, Hari; Afandi, Muhammad Misbahul; Siswanto, Deny Hadi (Universitas Ahmad Dahlan, 2025)
This study aims to develop a mathematics learning module based on a scientific approach with guided discovery to enhance the problem-solving skills of eighth-grade students. The research employs a development method following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The findings indicate that: (1) The developed learning module meets the criteria of validity, practicality, and effectiveness in improving students' mathematical problem-solving skills; (2) In terms of validity, the module is considered valid based on expert assessments, with an average score of 3,1 from module experts and 3.3 from subject matter experts, including lecturers and mathematics teachers; (3) Regarding practicality, the module is deemed practical based on student responses, with an average score of 3,16; (4) In terms of effectiveness, the Paired t-test results show a significance value (sig. 2-tailed) of 0,000 < 0,05, leading to the rejection of H0, indicating that the mathematics learning module is effective in enhancing problem-solving skills, with an improvement of 0,39 categorized as small. After using the module, all students (100%) scored above the minimum competency standard, with an average score of 83,96. Thus, the mathematics learning module based on a scientific approach with guided discovery meets the criteria of validity, practicality, and effectiveness in enhancing the problem-solving skills of 4 Sewon State Junior High School.